(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: Diffusion weighted imaging (DWI) has a wide range of applications in the evaluation of brain pathologies. This study was conducted to correlate Diffusion weighted MR imaging features of brain pathologies with other MRI sequences, to evaluate the role of DWI in brain pathologies. A prospective, observational and cross section study was performed of 100 patients in 6-month period. Patient with clinical suspicion of stroke, CNS infections, head injury, demyelination and tumor were included. All MRI studies were done on Siemens magneto essenza 1.5 T MRI. Age wise distribution, complaints, intra and extra axial location of tumor, presence and absence of restricted diffusion and findings of various sequences of MRI were studied. Methods: The present study was conducted in the Department of Radiology at AMC MET Medical college and LG hospital. Participants after understanding the study protocol and procedure were asked to give their written consent for the study. Results: in our study maximum cases were observed from 5th to 6th decades. 91 cases were intra-axial, 9 were extra-axial. 52% cases of stroke comprised of arterial infarct (39%), venous infarct (4%), HIE (3%), PRES (4%) and parenchyma haemorrhage (2%). 17% of cases were tumours which included glioma, metastases, GBM and hemangiopericytoma. 5% case of cavernous haemangioma and 5% cases of arachnoid cysts. 15% case of brain infections were included. All acute and subacute arterial infarcts and all venous infarcts showed restriction on diffusion weighted images and chronic cases did not show restriction. High grade gliomas, astrocytomas, and metastases showed diffusion restriction.